TINGKAT KESEJAHTERAAN PETANI ROTAN DI DESA BABAI KECAMATAN KARAU KUALA KABUPATEN BARITO SELATAN - Regina Arisandi; Ellyn Normelani; Deasy Arisanty (JPG (Jurnal Pendidikan Geografi), 2016)
This study entitled the welfare level of rattan farmers in Babai village, Karau Kuala district, southern Barito regency. The purpose of this study was to analyze the level of welfare of rattan farmers in the Babai village, Barito southern regency.The population in this study amounted 1600 heads of household with 310 samples, determination of this population by proportional random sampling technique. The primary data obtained through field observation and questionnaires (questionnaire), while secondary data obtained from the Central Statistics Agency (BPS) Southern Barito regency, Bappeda Southern Barito regency, Babai Village Office. The analysis technique used by using percentage technique.The results of the study showed that the stage of pre-prosperous family there are 25%, prosperous stage 1 there are 73%, while the stages of prosperous families there are 2%. Rattan farmer's welfare is unevenly because rattan prices often fluctuated. These situation has affect to result of rattan farmer income. Rattan farmer income in a week is Rp. 280,000, so within one month of rattan farmers get pay Rp. 1,040,000. The rattan farmers income is only sufficient for basic necessary and education of children, so for other necessary have not enough yet.Keywords: Level, Welfare, Farmer, Rattan.